Microalgae-Assisted Microbial Fuel Cell for Treatment of Difficult Waste Streams - Paulina Rusanowska; Marcin Dębowski; Marcin Zieliński (Energies, 2025)
Microalgae microbial fuel cells (pMFCs) are distinguished by their ability to combine waste utilization with the simultaneous recovery of energy and valuable materials. The generation of high current density is linked to the efficient electron transfer to the anode via the anodic biofilm and the high photosynthetic activity of the microalgae cultivated in the cathode chamber. This review explores the impact of wastewater type on energy production and wastewater treatment. Additionally, it discusses the challenges related to microalgae growth in the cathode chamber, the necessity of aeration, and the sequestration of carbon dioxide from the anode chamber. The efficiency of microalgae in utilizing nutrients from various types of wastewater is also presented. In conclusion, the comparison between wastewater treatment and energy balance in pMFCs and conventional wastewater treatment plants is provided. On average, MFCs consume only 0.024 kW or 0.076 kWh/kg COD, which is approximately ten times less than the energy used by activated sludge bioprocesses. This demonstrates that MFCs offer highly efficient energy consumption compared to traditional wastewater treatment systems while simultaneously recovering energy through exoelectrogenic, bioelectrochemical processes.